Reactivity to UV Radiation Exposure Monitoring Using Personal Exposure Devices for Skin Cancer Prevention: Longitudinal Observational Study - Bridget G Parsons; Elizabeth S Nagelhout; Ali P Wankier; Nan Hu; Riley Lensink; Angela Zhu; Katy Nottingham; Douglas Grossman; Jakob D Jensen; Yelena P Wu (JMIR Publications, 2021)
BackgroundEmerging UV radiation (UVR) monitoring devices may present an opportunity to integrate such technology into skin cancer prevention interventions. However, little is known about the effects of using a wearable UVR monitor on adults' and children's sun protection-related behaviors and attitudes (eg, cancer worry and perceived risk). Understanding the potential role of reactivity and seasonal effects will help inform the use of objective monitors in the context of skin cancer prevention research, including intervention studies. ObjectiveThe aim of this study is to examine the potential reactivity associated with a wearable personal UVR monitor, specifically the effects associated with reported sun-protective behaviors and skin cancer-related attitudes, which are often the targets of skin cancer preventive interventions. MethodsChild-parent dyads (n=97 dyads) were asked to wear a UVR monitoring device during waking hours for 2 weeks. Participants were asked to sync the device daily with a smartphone app that stored the UVR exposure data. Participants were blinded to their UVR exposure data during the 2-week period; thus, the smartphone app provided no feedback to the participants on their UVR exposure. Participants completed self-report questionnaires assessing sun-protective behaviors, sunburn, tanning, skin self-examination, skin cancer-related knowledge, perceived risk, cancer worry, response efficacy, and intentions to change behaviors over the 2-week period. Linear regressions were conducted to investigate changes in the outcomes over time and to account for the role of the season of study participation. ResultsRegression results revealed that there was a significant decrease over time for several sun protection outcomes in children, including time spent outdoors on weekends (P=.02) and weekdays (P=.008), sunscreen use (P=.03), reapplication (P<.001), and unintentional tanning (P<.001). There were no significant changes over time in children's and parents' UVR exposure, sunburn occurrence, or sun protection attitudes. Season of participation was associated with several outcomes, including lower sunscreen use (P<.001), reapplication (P<.001), sunburns (P=.01), intentions to change sun-protective behaviors (P=.02), and intentional (P=.008) and unintentional tanning (P=.01) for participants who participated in the fall versus the summer. ConclusionsThe findings from this study suggest that daily use of a UVR monitoring device over a 2-week period may result in changes in certain sun-protective behaviors. These results highlight the importance of identifying and addressing potential reactivity to UVR monitoring devices, especially in the context of skin cancer preventive intervention research. Ultimately, objectively assessed UVR exposure could be integrated into the outcome assessment for future testing of skin cancer prevention interventions.